Using Linked Data to Identify Pathways of Reporting Overdose Events in British Columbia, 2015 - 2017 - Graham, Eva; Zhao, Bin; Flynn, Mallory; Gustafson, Paul; Irvine, Michael; Slaunwhite, Amanda; Orpana, Heather; MacDougall, Laura; Kuo, Margot (International Journal of Population Data Science, 2022)
Introduction Overdose events related to illicit opioids and other substances are a public health crisis in Canada. The BC Provincial Overdose Cohort is a collection of linked datasets identifying drug-related toxicity events, including death, ambulance, emergency room, hospital, and physician records. The datasets were brought together to understand factors associated with drug-related overdose and can also provide information on pathways of care among people who experience an overdose. Objectives To describe pathways of recorded healthcare use for overdose events in British Columbia, Canada and discrepancies between data sources. Methods Using the BC Provincial Overdose Cohort spanning 2015 to 2017, we examined pathways of recorded health care use for overdose through the framework of an injury reporting pyramid. We also explored differences in event capture between linked datasets. Results In the cohort, a total of 34,113 fatal and non-fatal overdose events were identified. A total of 3,056 people died of overdose. Nearly 80% of these deaths occurred among those with no contact with the healthcare system. The majority of events with healthcare records included contact with EHS services (72%), while 39% were seen in the ED and only 7% were hospitalized. Pathways of care from EHS services to ED and hospitalization were generally observed. However, not all ED visits had an associated EHS record and some hospitalizations following an ED visit were for other health issues. Conclusions These findings emphasize the importance of accessing timely healthcare for people experiencing overdose. These findings can be applied to understanding pathways of care for people who experience overdose events and estimating the total burden of healthcare-attended overdose events. Highlights In British Columbia, Canada: Multiple sources of linked administrative health data were leveraged to understand recorded healthcare use among people with fatal and non-fatal overdose events The majority of fatal overdose events occurred with no contact with the healthcare system and only appear in mortality data Many non-fatal overdose events were captured in data from emergency health services, emergency departments, and hospital records Accessing timely healthcare services is critical for people experiencing overdose